Analysis of renewable energy potential in the Asia-Europe geographical axis - Alexandru Marius Tătar (Boletín Geográfico)
The limitation of conventional energy sources, on the one hand, and environmental concerns, on the other, have led countries increasingly to promote renewable energy technologies. Energy policy instruments play a crucial role in implementing innovation and reducing costs in renewable energy production. Countries deploy various policies to promote renewable energy technologies, such as capital subsidies, feed-in tariffs, tradable certificates, and renewable portfolio standards. However, some policies are more effective than others. Analyzing the renewable energy potential of advanced countries and combining these with indigenous factors is leading developing countries to create renewable energy technologies in their energy supply structures. This paper analyses the effect of different policy instruments in the renewable energy sectors in the Geographical Axis. Measures are analyzed and policy recommendations which, when considered, contribute to achieving renewable energy, thereby reducing emissions, mitigating climate change, and providing a clean environment and clean energy for all and future generations. It also investigated the opportunities associated with renewable energy sources, such as energy security.